The gut microbiome composition associates with bipolar disorder and illness severity. (April 2017) - Evans, Simon J.; Bassis, Christine M.; Hein, Robert; Assari, Shervin; Flowers, Stephanie A.; Kelly, Marisa B.; Young, Vince B.; Ellingrod, Vicky E.; McInnis, Melvin G.
Abstract: The gut microbiome is emerging as an important factor in regulating mental health yet it remains unclear what the target should be for psychiatric treatment. We aimed to elucidate the complement of the gut-microbiome community for individuals with bipolar disorder relative to controls; and test for relationships with burden of disease measures. We compared the stool microbiome from individuals with bipolar disorder (n = 115) and control subjects (n = 64) using 16S ribosomal RNA (rRNA) gene sequence analysis. Analysis of molecular variance (AMOVA) revealed global community case-control differences (AMOVA p = 0.047). Operational Taxonomical Unit (OTU) level analysis revealed significantly decreased fractional representation (p < 0.001) of Faecalibacterium after adjustment for age, sex, BMI and false discovery rate (FDR) correction at the p < 0.05 level. Within individuals with bipolar disorder, the fractional representation of Faecalibacterium associated with better self-reported health outcomes based on the Short Form Health Survey (SF12); the Patient Health Questionnaire (PHQ9); the Pittsburg Sleep Quality Index (PSQI); the Generalized Anxiety Disorder scale (GAD7); and the Altman Mania Rating Scale (ASRM), independent of covariates. This study provides the first detailed analysis of the gut microbiome relationships with multiple psychiatric domains from a bipolar population. The data support the hypothesis that targeting the microbiome may be an effective treatment paradigm for bipolar disorder.